Analysis of the spatial structure of meteor showers and associations of the KNURE catalog - Sakhno, D.G.; Ivanova, O.O.; Gorelov, D.Y. (Radiotekhnika, 2018)
The algorithm is proposed for calculating the density of a meteor streams in the standard perihelion of its average orbit – a numerical criterion by which dust-forming properties of meteor streams can be compared. It is shown that the most powerful meteor streams are characterized by the values of the large semi-axes a≈1 a.e., perihelion distances of 0.4 <q <0.8 a.e. and eccentricities e> 0.8. The meteor streams are detected, whose density exceeds the density of such a powerful stream as GEMINIDS (according to density in the standard perihelion of its average orbit).